La doble nacionalidad de personas naturales en el arbitraje de inversiones de Venezuela - Anzola, J. Eloy (2020)
An IPPA is a bilateral agreement for the promotion and protection of investments made by a person from one of the signatory states in the area of the other contracting state. Among the provisions of this treaty, compensation clauses are usually agreed upon the event that an expropriation dispute arises between an overseas investor and the host state. In this regard, it is mandatory that the investor be a natural person of one the parties to be compensated for any loss or damage suffered in relation to his covered investments.Then, the key question remains as to whether this bilateral agreement should also protect binational investors. Moreover, it might be well asked whether the international jurisprudence is uniform when an expropriation dispute arises. In this paper, the author analyzes the enforcement of a number of IPPAs signed by Venezuela, as well as the evolution of the criteria adopted by arbitral tribunals and courts. For this purpose, he first examines three recent claims against this State to highlight how the debate on the nature of the IPPA under international law has evolved, then he assesses the alleged lack of jurisdiction of the courts to rule in this matter and, at last, the nature of the investor and his dominant nationality.